Typification of the name 'Potentilla asturica' (Rosaceae) - Sáez Gonyalons, Llorenç; Aymerich, Pere (Mediterranean Botany, 2021)
Potentilla asturica, an Iberian endemic species included within sect. Recta, is typified.